2011
DOI: 10.1021/jo201732g
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Synthesis of Functionalized Spirobenzofuranones via MCR involving 3-Cyanochromones

Abstract: Another aspect concerning chromone chemistry leading to the one-pot synthesis of functionalized novel spirobenzofuranones has been described. The synthesis involves reaction of the zwitterionic intermediates formed by the 1:1 interaction between isocyanides and acetylenecarboxylates with 3-cyanochromones, whereupon through an unexpected and unprecedented reaction of the chromone moiety the isolated benzofuranones are formed. The regioselectivity of the reaction was investigated by DFT calculations. The geometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 67 publications
0
15
0
Order By: Relevance
“…It should be noted that the 3-cyanochromones react similarly with C-nucleophiles [31][32][33][34]. Recently obtained data has shown that these compounds are highly active and promising substrates for preparing a wide range of novel heterocycles with potential biological activity.…”
Section: Reactions Of 3-cyanochromones With Hydroxylaminementioning
confidence: 99%
“…It should be noted that the 3-cyanochromones react similarly with C-nucleophiles [31][32][33][34]. Recently obtained data has shown that these compounds are highly active and promising substrates for preparing a wide range of novel heterocycles with potential biological activity.…”
Section: Reactions Of 3-cyanochromones With Hydroxylaminementioning
confidence: 99%
“…Chromones bearing an electron‐withdrawing groups at position 3 revealed a variety of transformations upon treatment with nucleophilic reagents . Chromone‐3‐carbonitriles acquire the ability to undergo a nucleophilic 1,4‐attack followed by additional transformations related to γ‐pyrone ring opening and heterocyclizations at the C‐4 atom or at the cyano group . Herein, we aimed to study the reactivity of chromone‐3‐carbonitrile ( 1 ) toward a variety of nitrogen and carbon nucleophiles.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of the electron-withdrawing CN group at the 3-position of the chromone system changes the reactivity of the γ-pyrone ring with respect to nucleophiles and provides a broad synthetic potential of chromone-3-carbonitriles [1][2][3][4][5]. The diversity of properties of these compounds is because of the fact that they are highly reactive geminally activated push-pull alkenes (α,β-unsaturated ketones and nitriles simultaneously) with a good leaving group at the β-carbon atom, whose role is played by the phenolate anion.…”
Section: Introductionmentioning
confidence: 99%
“…Dihydro-5H,10H-bis[1]chromeno[2,3-b:3′,2′-J][1,10] phenanthroline-5,10-dione(3).A mixture of chromone-3-carbonitrile (1) (0.51 g, 3 mmol) or 2-amino-3-formylchromone (4) (0.57 g, 3 mmol) and cyclohexane-1,2-dione (0.34 g, 3 mmol), in absolute ethanol (20 mL) containing DBU (0.1 mL), was heated at reflux for 5 min. The yellow crystals obtained during heating were filtered off and crystallized from DMSO to give compound 3 as yellow crystals, mp > 320°C, yield (38-41%).…”
mentioning
confidence: 99%